Reporte de un caso clínico de Enfermedad de Weil de un paciente de raza negra : Report of a clinical case of Weil's disease in a black patient (La U Investiga, 2024)
Leptospirosis is considered a serious public health problem; it is a potentially endemic zoonotic infection, especially after heavy rains, it is produced by a spirochete of the genus Leptospira, Leptospira interrogans, although there are 210 serovars, only 21 are pathogenic for animals and humans, is distributed in tropical regions, less frequently in temperate zone regions. The human being is exposed by coming into contact with injured skin or mucous membranes with contaminated water or urine of carriers, mainly rodents or other mammals, for which he is propitious, ingestion or contact without protection of goggles, footwear or gloves. Predispose to disease. The clinic varies from an asymptomatic or mild anicteric form to an icteric form (Weil's syndrome) characterized by greater systemic involvement and mortality. We present the case of a 36-year-old male with a clinical picture characterized by jaundice, fever, abdominal pain, myocarditis, pancreatic enzyme abnormalities, acute kidney failure, and liver failure. Which required, due to its failures, initial support treatment in intensive care and later in the Internal Medicine service that evolved favorably until discharge.